Using the Principles of Assisted Reading to Improve Fluency in the Performance of a Student with Language Based Learning Disabilities - Graham, Sheila; Porter, Joel; DeNault, Nicole (My University, 2000)
Through this single subject study, it is suggested that alllomaticity and speed can limitedly improve fluency in a learning disabled student athlete not only in learning new skills cognitively, but also in athletic performance. The coach stated that one of his student athletes was having great difficulty remembering the plays and he wanted to know if it was possible to develop a plan to enhance the player's ability to read and remember the plays. The intervention of assisted reading couples the two principles of speed and word recognition resulting in the study participant reading faster with less word recognition errors on each repeated reading, reinforcing the text with tape recorded backups and video illustrations, and thus performing more automatically wilh less hesitation.
Keywords: athletic performance; skills